Value For Money : Suatu Analisis Pengaruh Kinerja Pemerintah Desa terhadap Pengelolaan Keuangan Desa pada Desa Subun Bestobe - Marisa S. B Seran (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
The background of this research is the phenomenon of very good village fund management, so that it becomes very effective and efficient in its use, even though in very unsupportive conditions due to the covid-19 outbreak. The purpose of this study was to determine the performance of Subun Bestobe Village Financial Management using the value for money (VFM) method, namely with measurement indicators (economical, efficiency, and effectiveness). The results showed that the economic level for the last 5 years was in the >100% category, thus meeting the economic standard of value for money. The efficiency level for the last 5 years is at the standard >40%, the ratio is above 100% so that the efficiency ratio does not meet the efficient value for money standard. The effectiveness ratio for the last 5 years has met the standard so that it shows that the Subun Bestobe Village Government has been effective in managing village finances for the village community. This is because the effectiveness of financial management can increase if the village community is satisfied with the performance of good financial management, especially in village development. So that in the future the village can become a superior, independent and competitive village.